The Levels of Transformational Leadership (TL) Practice and its Impact on the Organizational Health (OH) of School Teachers in Selangor and Perak: A Systematic Review - Armugam , Manimaran; Ismail, Ramlee; Sedhu, Daljeet Singh (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2021)
The main purpose of this review is to explore the relationship between transformational leadership and organizational health in the context of leadership practices in schools. This review also aims to look at the characteristics of transformational leadership and how transformational leadership is created from various basic leadership theories. The methodology used is a systematic review in which n = 34 articles were selected for review after the filtering process based on a number of pre-determined criteria. This systematic review found that there was a correlation between the transformational leadership aspects introduced by Bass and the organizational health elements introduced by Hoy and Miskel. This is very important because it forms the basis of this research. The four aspects of transformational leadership, namely ideal influence, inspirational motivation, intellectual stimulation and individual consideration are related to organizational health elements, namely, integrity in institutions, collegial leadership, relationships between teachers and academic emphasis.